Wybrane cechy szyszek jodły pospolitej Abies alba Mill. w aspekcie procesu wyłuszczania i jakości nasion - Aniszewska, Monika; Brzózko, Jacek; Zychowicz, Witold (Leśne Prace Badawcze, 2018)
Fir cones Abies alba Mill. are not as extensively described in the literature as cones of other species and therefore there is no description of the changes in water content and their dynamics during the extraction process. Developing a mathematical model describing these changes based on cone parameters and air temperature is a step forward to determine the optimal conditions for the extraction process. Here we present such a model derived using fresh cones collected in a seed production stand in the Zwoleń Forest District (RDSF Radom). For 120 randomly chosen cones, the length and the largest diameter of the cone were measured, using the Multiscan program. In addition, for 60 randomly selected cones, the diameter was measured along the entire length of the cone at 10 mm intervals. This allowed us to generate cone models approximating rotational solids for which the outer surface area was calculated using a fourth degree polynomial function and the obtained area was then used to determine cone volume. To facilitate the generalization of surface area and volume calculations to other cones, the ks1 and ks2 coefficients were derived, which simplified the employed formulas without significantly affecting accuracy. Analogous analyses were also carried out for cone stems, which allowed the process of seed extraction from cones to be described by mathematical equations. The stem of the cone was found to constitute 2.6% of its volume and 4% of its dry mass. An exponential equation was used to describe the mass change of the cone during the seed extraction process, in which the parameters are the initial and final water content in the cone and the power factor b, which is a function of the cone thickness. For the extracted seeds, energy content and germination rate were determined 14 and 28 days after sowing. The seeds obtained in the investigated extraction process did not reach first grade quality.